Strojno učenje: S Pythonom do prvega klasifikatorja - Karakatič, Sašo; Fister ml., Iztok (University of Maribor Press, 2022)
Machine Learning: Classification in Python. The book serves as an introduction to the field of machine learning for anyone with basic programming experience. Important concepts of machine learning (knowledge model, learning and test set, learning algorithm) are reviewed. More details are given for the classification technique and quality evaluating procedures of classification knowledge models. The classification algorithm k nearest neighbors is presented - both conceptually and in program code. The book provides many examples in the Python programming language and the Jupyter Notebooks environment. For the purpose of consolidating knowledge, several computational and programming exercises with the given solutions are offered.